Digital Literacy Training to Increase Data Privacy AwarenessAmong High School Students in Tangerang (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
The development of digital technology has had a significant impact on daily life, including for high school students in Tangerang. However, a lack of awareness about the importance of protecting personal data privacy can increase the risk of misuse of personal information. This Community Service activity aimed to conduct digital literacy training to enhance students’ understanding of data privacy. The method used included an interactive approach involving material delivery, discussions, and Q&A sessions that focused on understanding technology, data protection strategies, and the application of digital ethics. The results showed that digital literacy training was effective in raising students' awareness of personal information security, such as using strong passwords, enabling two-step verification, and recognizing cyber threats such as phishing and hacking. Furthermore, the training encouraged students to act more responsibly in the digital world, thereby fostering a safer online environment. Thus, digital literacy training is an essential aspect of equipping students with the necessary skills and insights to navigate the digital era safely and wisely.